Influence of dynamic loadings from operating of underground railway on the deflected mode of high-rise buildings - Дзюба, А.В.; Миронець, Т.Л. (Proceedings of National Aviation University (archive), 2010)
Influence of motion of train of underground passage on height housing building is considered. Recommendations in relation to protecting of buildings and buildings from a vibration are given. Basic from them: to increase building inflexibility; to apply barriering constructions in the array of soil.